JENIS-JENIS GLOMEROMYCOTA DI PANDANUS TECTORIUS DARI JAWA DAN MADURA - Kartini Kramadibrata (Floribunda, 2013)
Glomeromycota is a group of arbuscular fungi (AF) which usually grow on rhizosphere of higher plants either dicots or monocots, and lower plants. Information on its diversity, particularly in Indonesia remains underexplored. As a result, this study is carried out in order to fill the gap on the information of Glomeromycota diversity surrounding Pandanus tectorius. The soil samples were collected from Pandanus grow in coastal forests in southern part of West Java, villages in West, Central and East Java including Madura Island. Glomeromycota spores were isolated from soils around rhizosphere of pandan and were identified using their morphological characters. Ten species of Glomeromycota were associated with pandan rhizosphere that belong to genera Acaulospora (3 species), Claroideoglomus (1 species), Funneliformis (1 species), Glomus (2 species), Racocetra (1 species), Sclerocystis (2 species), and Glomus glomerulatum is a new record for Java. The record of each species is presented